FEEDING FISH WITH INSECTS: A SUSTAINABLE AND NATURAL APPROACH - Mardiyeva Baxora Xusniddinovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article examines the use of insects as an alternative feed source for fish in aquaculture and fish farming systems. It highlights the nutritional value of insects, their role as a natural component of fish diets, and their potential to replace conventional feed ingredients such as fishmeal and soybean meal. The article also discusses environmental, economic, and practical benefits of insect-based feeds, as well as challenges related to large-scale adoption. By synthesizing existing research and industry practices, the article demonstrates how insect feeding can contribute to sustainable aquaculture and reduced environmental impact.